Characteristics of ultrafine particle emission from light-vehicle engine at city transport-speed using after-treatment device fueled with n-butanol-hydrogen blend. (June 2021) - Yusuf, Abdulfatah A.; Yahyah, Hadijah; Farooq, Atiku A.; Buyondo, Kasumba A.; Olupot, Peter W.; Nura, Sharif S.; Sanni, Tajuddeen; Hannington, Twinomuhwezi; Ukundimana, Zubeda; Hassan, Abdurrahman S.; Mundu, Mustafa M.; Samede, Sibuso S.; et al.
Abstract: In recent times, the extinction of fossil fuel resources and emission of harmful pollutants have persuaded the researchers to obtain alternative and renewable fuels. Consequently, in the present experimentation, a ternary fuel blend was acquired and analysed in a modified turbocharged gasoline direct injection (GDI) engine as a feasible alternative to neat fossil fuel. Experiments were carried out using a blend of 8% n-butanol and 8% mass fraction of hydrogen with gasoline fuel at city transport speed mode under stoichiometric and air-fuel ratio of 1.0. Butanol and hydrogen were blended with the gasoline due to their satisfying thermodynamic properties and combustion reactivity. The result shows gradual reduction of particles emitted with n-BH16 by 1.06 × 10 11 particles/hr as compared to n-BH00 at 1.89 × 10 12 particles/hr. For all fuels, the smallest particles measured by Engine Exhaust Particle Sizer (EEPS) were no longer detectable at phase 2 from 548 s to 789 s due to low concentrations. However, the gaseous emission of the n-BH16 fueled engine varies with 28 g/kW.h decrement in fuel consumption (FC), while increasing hydrocarbon (HC) emission. As a result, ultra-particles decreased in nucleation mode, which in-turn lead to minimum combustion duration and cylinder gas pressure. Adaptation of n-BH16 fuel blend in light-duty GDI engines might serve as a potential to meet the new particulate emission regulations and improve toxic air contaminant.